Coordination of 1,10-phenanthroline and 2,2′-bipyridine to Li + in different ionic liquids. how innocent are ionic liquids? - Schmeißer, Matthias; Heinemann, Frank Wilhelm; Illner, Peter; Puchta, Ralph; Zahl, Achim; van Eldik, Rudi (Inorganic Chemistry, 2011)

Coordination of 1,10-phenanthroline and 2,2'-bipyridine to Li+ in different ionic liquids. How innocent are ionic liquids? - Schmeißer, Matthias; Heinemann, Frank Wilhelm; Illner, Peter; Puchta, Ralph; Zahl, Achim; van Eldik, Rudi (Inorganic Chemistry, 2011)
On the basis of (7)Li NMR measurements, we have made detailed studies on the influence of the ionic liquids [emim][NTf(2)], [emim][ClO(4)], and [emim][EtSO(4)] on the complexation of Li(+) by the bidentate N-donor ligands 2,2'-bipyridine (bipy) and 1,10-phenanthroline (phen). For each of the employed ionic liquids the NMR data implicate the formation of [Li(bipy)(2)](+) and [Li(phen)(2)](+), respectively. X-ray diffraction studies were performed to determine the coordination pattern in the solid state. In the case of [emim][ClO(4)] and [emim][EtSO(4)], crystal structures confirmed the NMR data, resulting in the complexes [Li(bipy)(2)ClO(4)] and [Li(phen)(2)EtSO(4)], respectively. On the contrary, the ionic liquid [emim][NTf(2)] generated the C(i) symmetric, dinuclear, supramolecular cluster [Li(bipy)(NTf(2))](2), where the individual Li(+) centers were found to be bridged by two [NTf(2)] anions. Density functional theory (DFT)-calculations lead to further information on the effect of stacking on the coordination geometry of the Li(+) centers.

Coordination of terpyridine to Li+ in two different ionic liquids - Pokorny, Klaus; Schmeißer, Matthias; Hampel, Frank; Zahl, Achim; Puchta, Ralph; van Eldik, Rudi (Inorganic Chemistry, 2013)

Gutmann donor and acceptor numbers for ionic liquids - Zahl, Achim; van Eldik, Rudi; Puchta, Ralph; Schmeißer, Matthias; Illner, Peter (Chemistry - A European Journal, 2012)

Ligand exchange processes on solvated lithium cations. VI. Determination of coordination numbers by ligand substitution and 7Li NMR - Schmeißer, Matthias; Zahl, Achim; Scheurer, Andreas; Puchta, Ralph; van Eldik, Rudi (Journal of the American Chemical Society, 2010)
On the basis of 7Li NMR studies the coordination mode of phenantroline (phen) and bipyridine (bipy) to Li+ ions was found to be [Li(phen)2]+ and [Li(bipy)2]+ in the weakly coordinating solvent nitromethane. A large chemical shift of the 7Li signal indicated a strong interaction between the ligand and the metal center. The related sp2-hybridized N-donor ligand 2, 2′-bis[(4S)-4-benzyl-2-oxazoline] (biox) showed a negligible effect on the 7Li shift, suggesting that almost no interaction occurs between the Li+ center and biox as compared to Li+ and the solvent γ-butyrolactone. Corresponding DFT (RB3LYP/LANL2DZp) calculations have clearly indicated that the poor coordination of biox is not caused by steric effects but rather by the electronic nature of the heterocyclic biox system. © 2010 Verlag der Zeitschrift für Naturforschung.
UnivIS-Import:2015-10-26:Pub.2010.nat.dchph.laoc1.ligand
Keywords: DFT calculations; Lithium complex formation; N chelates

Reply to the Comment on the Article "Gutmann Donor and Acceptor Numbers for Ionic Liquids" (Chem. Eur. J. 2012, 18, 10969-10982) by J.-F. Gal and C. Laurence - Schmeißer, Matthias; Illner, Peter; Puchta, Ralph; Zahl, Achim; van Eldik, Rudi (Chemistry - A European Journal, 2013)